1997
DOI: 10.1002/stem.150368
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Precursor Cells are Found in CD34 + Cells from Human Bone Marrow

Abstract: It is known that osteoblast precursor cells are found in the low-density mononuclear (LDMN) fraction of human bone marrow (BM) aspirates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 24 publications
6
78
0
Order By: Relevance
“…In addition to the classical bone marrow stromal cells [2], it is possible that bone marrow non-adherent cells, as previously identified by Long et al [3,4] access the BRC via this mechanism, or that circulating osteoblastic cells contribute to the pool of osteoblastic cells entering the BRC. On the other hand, given the potential overlap between osteoblastic and endothelial cells noted in the present and previous work [21,22,25], and the evidence that vascular pericytes can differentiate into osteoblasts [26], as well as recent work demonstrating the pericytes, themselves, may arise from a CD34 pos progenitor in the vessel wall [27], it is also possible that precursor cells in the vasculature (i.e., within the capillary wall penetrating the BRC) give rise to osteoblastic progenitors. Clearly, additional studies are needed to test these hypotheses and to further identify the source of the circulating OCN and AP expressing cells as well as their possible role in bone remodeling.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to the classical bone marrow stromal cells [2], it is possible that bone marrow non-adherent cells, as previously identified by Long et al [3,4] access the BRC via this mechanism, or that circulating osteoblastic cells contribute to the pool of osteoblastic cells entering the BRC. On the other hand, given the potential overlap between osteoblastic and endothelial cells noted in the present and previous work [21,22,25], and the evidence that vascular pericytes can differentiate into osteoblasts [26], as well as recent work demonstrating the pericytes, themselves, may arise from a CD34 pos progenitor in the vessel wall [27], it is also possible that precursor cells in the vasculature (i.e., within the capillary wall penetrating the BRC) give rise to osteoblastic progenitors. Clearly, additional studies are needed to test these hypotheses and to further identify the source of the circulating OCN and AP expressing cells as well as their possible role in bone remodeling.…”
Section: Discussionsupporting
confidence: 56%
“…Of interest, Chen et al [21] have previously demonstrated that bone marrow CD34 pos cells are capable of differentiating into osteoblastic cells in vitro and forming mineralized nodules, although the ability of these cells to form bone in vivo was not tested in that study. These investigators also found that CD34 expression was rapidly lost by these cells in vitro under osteoblast differentiating conditions, suggesting the possibility that the CD34 positive fraction of OCN positive cells may represent a more primitive population, although further work is needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Based on cell shape, we believe that the RANKL-positive cells ( Figure 2D) most likely represent preosteoblastic cells which have been shown to express RANKL and have a round morphology in other studies. 20,21 The RANKL-positive cells in our samples displayed a round morphology, suggesting that they are not fibroblasts, which appear spindle-like, nor are they osteoblasts, which assume a cuboidal shape. 22,23 Other groups have noted the in vivo expression of RANKL by PDL cells through immunohistochemistry and RT-PCR in the compression side after one day of orthodontic force, but did not look at earlier time points.…”
Section: The Rat Otm Model Accurately Replicates the Cellular And Molmentioning
confidence: 84%
“…[57][58][59][60][61][62][63] However, MSCs are present at low frequency in bone marrow and in the circulation. 64 Despite the lack of cellular and molecular tools and in vivo assays that permit the rigorous identification of stem cells from mesenchymal tissues, it is known that a cell population with MSC-like characteristics can be isolated based on its ability to adhere to plastic and may be partially purified by separation techniques.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%